PEMANFAATAN KULIT KACANG TANAH (Arachis hypogeae) UNTUK MEMBUAT MINYAK AROMATIK SEBAGAI PETUNJUK PRAKTIKUM PADA BAB BIOTEKNOLOGI - Lilik Mawartiningsih (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2017)
Instructions lab at the high school level (school SMA) on the subject of biotechnology is one of the practical guide developed by using other organisms to produce a new product that can be useful for daily life hari.Masalah in this study, namely how the compounds exist in peanut skin, and how the process of making aromatic oil from peanut skin waste?. This type of research is experimental. From the third experiment result using ethanol blend, groundnut peanut powder, and aquades with 50 ml: 5 gr: 50 ml, gives the desired result of producing aromatic oil.